Review of the Epeolus tarsalis species group (Hymenoptera: Apidae, Epeolus Latreille, 1802), with description of a new species - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2021)
The five species of Epeolus tarsalis species group are reviewed. One new species, Epeolus mikhailovi sp. nov. (Kyrgyzstan, Tajikistan), is described and illustrated. Epeolus melectiformis Yasumatsu, 1938 is newly recorded from China, and E. tarsalis Morawitz, 1874 is newly recorded from Kazakhstan. The distribution data for other species are supplemented. An identification key for both sexes of this species group is presented.